Problems and suggestions regarding professional practice for master of public health graduates in China - Weiquan ZENG; Yi LIN; Zhuoxuan LIANG; Huan YAO; Guanhao HE; Xiaomei DONG; Tao LIU; Xiaofeng LIANG; Wenjun MA (Zhongguo gonggong weisheng)
Public health, as a highly practical discipline, has gained increasing attention following the novel coronavirus disease (COVID-19) pandemic. Professional practice is a crucial component in the training of Master of Public Health (MPH) postgraduates, who represent high-level public health professionals. High-quality practical training is essential for ensuring the quality of MPH education. Currently, there are several challenges in the professional practice-based teaching of MPH students in China, including a singular type of practice bases and a lack of standards and norms for base construction; the absence of detailed practical teaching manuals and authoritative teaching materials; a lack of training for base instructors; unclear, vague, and monotonous practical teaching requirements and content; unclear responsibilities and an ineffective coordination mechanism between university and field instructors; and low student enthusiasm for field practice coupled with an imperfect assessment and evaluation system. This article summarizes the existing problems in professional practice-based teaching for MPH students in China and proposes corresponding suggestions, aiming to provide a reference for improving the quality of practical teaching for MPH professionals in the country.